Three-Dimensional Core-Branch α-Fe2O3@NiO/Carbon Cloth Heterostructured Electrodes for Flexible Supercapacitors - Zhang, Miao; Li, Xifei; Wang, Xiaohua; Li, Dejun; Zhao, Naiqin (Frontiers in Chemistry, 2020)
A convenient and scalable hydrothermal method is developed for the fabrication of the core-branch Fe2O3@NiO nanorods arrays directly grown on flexible carbon cloth (denoted as Fe2O3@NiO/CC). Such a unique architecture can be applied as an excellent electrode of flexible supercapacitors. As a result, the Fe2O3@NiO core-branch hybrid nanorods array exhibit a high capacitance ~800 mF cm−2 (about 10-fold increase in areal capacitance with respect to pristine Fe2O3 nanorods array ~200 mF cm-2 at current rates 10 mA cm-2) with long-term cyclic stability (2.7 % capacitance loss after 4000 cycles) and remarkable rate capability (56 % capacitance retention at a very large current density of 100 mA cm-2), which should be ascribed to the reduction of the contact resistance and the free-standing structure of the flexible electrode. This study provides a novel strategy to construct high-performance flexible electrode materials with unique core-branch structure by incorporating two different pseudocapacitive materials.